Grassy-ELM regime with edge resonant magnetic perturbations in fully noninductive plasmas in the DIII-D tokamakaEdge-localized-mode. (27th July 2018) - Nazikian, R.; Petty, C.C.; Bortolon, A.; Chen, Xi; Eldon, D.; Evans, T.E.; Grierson, B.A.; Ferraro, N.M.; Haskey, S.R.; Knolker, M.; Lasnier, C.; Logan, N.C.; et al.
Abstract: Resonant magnetic perturbations ( n   =  3 RMPs) are used to suppress large amplitude ELMs and mitigate naturally occurring 'grassy'-ELMs in DIII-D plasmas relevant to the ITER steady-state mission. Fully non-inductive discharges in the ITER shape and pedestal collisionality (   ≈  0.05–0.15) are routinely achieved in DIII-D with RMP suppression of the Type-I ELMs. The residual grassy-ELMs deliver a low peak heat flux to the divertor as low as 1.2×  the inter-ELM heat flux in plasmas with sustained high H-factor ( H 98y2   ≈  1.2). The operating window for the RMP grassy-ELM regime is q 95   =  5.3–7.1 and external torque in the range 9–0.7 Nm in the co-Ip direction, which is in the range required for a steady-state tokamak reactor. The RMP grassy-ELM regime is associated with a two-step pedestal, with strong flattening of the density around the zero crossing in the E   ×   B shear. The edge magnetic response of the plasma to the n   =  3 RMP is found to be  ≈2–3×  larger than for comparable ITER baseline plasmas ( β N   ≈  1.8, q 95   ≈  3.1). The amplification of the RMP is consistent with the weak magnetic perturbation level ( δB / B   ≈  1  ×  10 −4 ) required for effective Type-I ELM suppression. Cyclic variations in the pedestal pressure, width, and toroidal rotation are observed in these plasmas, correlated with cyclic variations in the strength and frequency of the grassy-ELMs. Extended MHD analysis and magnetic measurements indicate that these pedestal pulsations are driven by cyclic variations in the resonant field strength at the top of the pedestal. These pedestal pulsations reveal that the grassy-ELMs is correlated with the proximity of the pedestal to the low- n peeling-ballooning mode stability boundary. The use of low amplitude magnetic fields to access grassy-ELM conditions free of Type-I ELMs in high beta poloidal plasmas ( β P   ≈  1.5–2.0) opens the possibility for the further optimization of the steady-state tokamak by use of edge resonant magnetic perturbations.